Draft Outline Seventh Five Year Plan Andhra Pradesh 1985-90 Volume-I - Planning Commission (Planning Commission, 1985)
Andhra Pradesh constituted in 1956 composing of most Telugu speaking people, has an area of 2.77 lakh sq.kms. and a population of 54 million (1981). It ranks as 5th largest State both in terms of area and population in the Indian Union. The State is a tropical region and has a long coast line. While some coastal areas have the benefit of assured irrigation, the northern and north-western parts are rich in mineral resources.
Finance and Planning (PLG. Wing) Department, Government of Andhra Pradesh